Autorzy:Praca zbiorowa
Wydawnictwo:WSiP
Rok wydania:2013
Usuń niewymierność z mianownika ułamka 4.5 gwiazdek na podstawie 6 opinii

Usuń niewymierność z mianownika ułamka

5Zadanie
6Zadanie
7Zadanie
8Zadanie
9Zadanie
10Zadanie

`a)\ 4/sqrt5=(4sqrt5)/(sqrt5*sqrt5)=` `(4sqrt5)/5` 

`b)\ (3sqrt3)/sqrt6=` `(3sqrt3*sqrt6)/(sqrt6*sqrt6)=` `(3sqrt18)/6=` `sqrt18/2=` `(sqrt9*sqrt2)/2=(3sqrt2)/2` 

`c)\ (2+sqrt5)/(3sqrt2)=` `((2+sqrt5)*sqrt2)/(3sqrt2*sqrt2)=` `(2sqrt2+sqrt10)/(3*2)=` `(2sqrt2+sqrt10)/6` 

`d)\ 2/root3(5)=` `(2*root3(5)*root3(5))/(root3(5)*root3(5)*root3(5))=` `2root3(25)/5` 

`e)\ 3/(2root3(3))=` `(3root3(3)*root3(3))/(2root3(3)*root3(3)*root3(3))=` `(3root3(9))/(2*3)=` `root3(9)/2` 

`f)\ (3+root3(5))/root3(2)=` `((3+root3(5))*root3(2)*root3(2))/(root3(2)*root3(2)*root3(2))=` `((3+root3(5))*root3(4))/2=` `(3root3(4)+root3(20))/2` 

`g)\ sqrt2/(sqrt2-1)=` `(sqrt2*(sqrt2+1))/((sqrt2-1)(sqrt2+1))=` `(2+sqrt2)/(sqrt2^2-1^2)=` `(2+sqrt2)/(2-1)=2+sqrt2` 

`h)\ (sqrt27)/(sqrt3+1)=` `(sqrt27*(sqrt3-1))/((sqrt3+1)(sqrt3-1))=`  `(sqrt81-sqrt27)/(sqrt3^2-1^2)=` `(9-sqrt9*sqrt3)/(3-1)=` `(9-3sqrt3)/2`